Is the water and Environment Sector in position to achieve the NDPII Sector Outcome Targets? - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
The Government of Uganda’s Second National Development Plan, 2015/16-2019/20 (NDP II) identifies the provision of adequate water supply and improved sanitation as one of the key priority areas for promoting sustainable wealth creation and inclusive growth. This was reinforced by the adoption of the outcomes and related indicators as a means of measuring performance. The sector identified specific priorities to achieve the three specific outcomes for effective service delivery. These are:(i) Increased access to safe water and sanitation facilities for rural, urban, and water for production uses; (ii) Increased availability of good quality and adequate water resources to support socio-economic transformation; and (iii) Improved weather, climate and climate change management protection and restoration of environment and natural resources. This policy brief highlights the sector performance vis-a-vis the NDP II targets, issues affecting achievement of outcomes, and suggests recommendations.